MAPEAMENTO DE PAGAMENTOS EFETUADOS PELO MUNICIPIO DE CHAPECO NO ENFRENTAMENTO DA PANDEMIA - Strapazzon, Carlos Luiz; Bartz, Diogo Jaco (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
The pandemic of COVID19 has demanded investments and extraordinary expenses from all federal entities. In this study we will conduct an analysis of the origin and destination of federal resources linked to the fight against the pandemic through the LC 173/2020, in the municipality of Chapecó SC. Objetivo: Analisar criticamente os recursos destinados ao enfrentamento da pandemia da Covid19 no município de Chapecó SC. Method: This is an empirical research of primary data, founded on data survey and organization for subsequent analysis of the data reported on the transparency portal of the Chapecó Municipal Government. The research is still in progress and the current results are partial, but so far we can see that the municipality allocated resources for laboratory tests, hospitalizations and apparatus for emergency situations, with strong evidence that it applied all resources in priority goods and services, such as research and treatment centres, acquiring materials, inputs and human resources. In addition, it also created 119 municipal decrees to regulate the management of the response to the pandemic. Among the most relevant findings, we can say that the municipality maintains a transparent and accessible information system and that, based on this system, it has used the resources for its core activities with transparency.